2021
DOI: 10.22219/jrak.v11i3.17689
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model to Predict Cheating on Online Exam Among Accounting Students: Does Islamic Religiosity Matter?

Abstract: The purpose of this study is to empirically examine a model of cheating behavior of accounting students on online exams to determine the factors that influence the intention of accounting students to cheat on online exams. Based on the literature review, the factors that influence the intention of accounting students to cheat on online exams are identified in the scope of Ethics Theory (deontological and teleological evaluation), Theory of Planned Behavior, and Islamic Religiosity. The data were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…In addition, prior studies have also confirmed Islamic religiosity as a determinant of financial behavior, including charity (Chetioui et al, 2023), indebtedness (Chetioui et al, 2023), CSR (Shu et al, 2022), and buying behavior (Handriana et al, 2021). In other fields, religiosity has also been confirmed to affect students' fraudulent intentions and attitudes (Kholid et al, 2021), tax evasion (Atmoko, 2022), and auditor independence (Saputri & Nur, 2020). Hence, our study opens a preliminary discussion regarding the relationship between Islamic religiosity on financial behavior and financial well-being in college students.…”
Section: Introductionsupporting
confidence: 73%
“…In addition, prior studies have also confirmed Islamic religiosity as a determinant of financial behavior, including charity (Chetioui et al, 2023), indebtedness (Chetioui et al, 2023), CSR (Shu et al, 2022), and buying behavior (Handriana et al, 2021). In other fields, religiosity has also been confirmed to affect students' fraudulent intentions and attitudes (Kholid et al, 2021), tax evasion (Atmoko, 2022), and auditor independence (Saputri & Nur, 2020). Hence, our study opens a preliminary discussion regarding the relationship between Islamic religiosity on financial behavior and financial well-being in college students.…”
Section: Introductionsupporting
confidence: 73%
“…Thus, attitudes are important for many factors for online evaluation. First, attitudes of students regarding student cheating behaviors in online exams are correlated (Kholid et al, 2021;Reedy et al, 2021). So, negative attitudes affect the intention to cheat on online exams.…”
Section: Discussionmentioning
confidence: 99%
“…They found that online assessment evaluation activities and exam types significantly affected student achievement scores. However, Kholid (2021) found that perceived behavioral control, subjective norm, attitude, and perceived benefits positively affect the intention to cheat on online exams. While there are mixed attitudes towards online exams, students view them favorably due to their flexibility and convenience.…”
Section: Introductionmentioning
confidence: 94%